Pengaruh Penambahan Serat Batang Pisang Kepok (Musa Pasadisianca) Terhadap Kuat Tekan Batako - Muhammad Andrean Bintara Adyanto; Gatut Rubiono; Ikhwanul Qiram (Virtual of Mechanical Engineering Article, 2022)
Research has been carried out with the aim of obtaining the effect of adding "kepok" banana fiber (Musa Pasadisianca) to the compressive strength of the brick. The study was conducted in a true experiment with variations in the ratio of the addition of banana fiber by 1.6; 2.5; and 3.3 gram. applying pressure to each specimen in variation 3; 5; and 7 N/m, the compressive strength test was carried out to obtain the mechanical properties of the product. The results showed that the percentage decrease in mass and product dimensions increased along with the pressure applied to the specimen. Depreciation of the mass of brick products is accompanied by changes in the value of the water content of the product. The compressive strength of the bricks increases with the percentage of the given fiber weight. Keywords: compressive strength, concrete brick, fiber, kepok banana (musa pasadisianca), mix ratio.